Pengaruh Tax Avoidance Terhadap Cost Of Debt Dan Dampaknya Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2017) - Raden Wulan Saparinda (Universitas Ma'soem, 2020)
The purpose of this research is to analyze tax avoidance on the cost of debt and it affects the firm value. This research uses a sample of manufacturing companies on the Indonesia Stock Exchange for the period 20152017. The program used in analyzing data uses SPSS 21 . This research found that tax avoidance has a positive influence on the cost of debt t test showing significance of 0.003 <0.05. Cost of Debt has a negative effect on firm value with a significance of 0,000 <0,05. Tax avoidance does not affect on firm value because of the significance of 0.052> 0.05. The cost of debt can mediate the effect of tax avoidance on firm value with a significance of 0.025 <0.05. The path analysis results is a direct effect of X on Y by 9,1%, direct effect of Y on Z by 15,84% and there is an indirect effect of X on Z through Y by -12%.